2010
DOI: 10.1017/s0317167100010015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Stroke in Pakistan: A Dedicated Stroke Clinic Experience

Abstract: Background: Secondary prevention of cerebrovascular disease through dedicated stroke clinics has been shown to decrease recurrent vascular events in patients. However, there is limited literature describing such stroke clinic experiences from low and middle income countries. This study describes patient characteristics and observations made at the first systematized stroke clinic in Pakistan. Methods: A retrospective audit of medical records of all patients presenting between September 2006 and August 2008 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
(17 reference statements)
3
21
0
Order By: Relevance
“…Our findings of hypertension replicate the findings of hypertension in a study conducted in Karachi Taj F et al [16] and also our values regarding Hypertension is in near range of studies [17,18]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings of hypertension replicate the findings of hypertension in a study conducted in Karachi Taj F et al [16] and also our values regarding Hypertension is in near range of studies [17,18]. …”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that n = 24, 48% among cases were diabetic having p = 0.010, odd ratio of 2.49 and relative risk of 1.7. Our study findings in perspective of Diabetes Mellitus are in near range of studies [24,25]. …”
Section: Discussionsupporting
confidence: 71%
“…17 This is similar to earlier studies 18–21 (Table 3). In young stroke, common causes of stroke detected were infective meningitis (tuberculosis and bacterial) and hypertension (for haemorrhagic stroke), predominantly in men.…”
Section: Stroke In Pakistansupporting
confidence: 92%
“…[3][4] Stroke is significantly higher in old age group but previous data reveals 18% of the cases are younger, which is a strong indicator for Pakistan with the fact that a large proportion of our population is young adults. [5][6][7] Previous data regarding the rate of risk factors of stroke reveals that the common risk factors in younger age group are dyslipidemia, diabetes mellitus, hypertension and smoking.…”
Section: Introductionmentioning
confidence: 90%